Perfil de demandas medico/paciente em cirurgia plástica no Rio Grande do Sul - Silva, Dione Batista Vila-Nova da [UNIFESP] (2016)
INTRODUCTION: Plastic Surgery has a high rate of judicial process of patient against physician in all over the words. This may be related to a lack of Informed Consent, poor cosmetic results, such as scar and other factors as little experience of involved surgeons. PURPOSE: To compare the profile of patient against physician of judicial process related to Plastic Surgery in Rio Grande do Sul, São Paulo and Rio de Janeiro. METHODS: were selected patient/physician lawsuits in Plastic Surgery in the web site of each one of the State court of justice: www.tjrs.jus.br, www.tjsp.jus.br, www.tjrj.jus.br from the year 2009 to 2012. They were collected and compared data from the final sentences in the "Full Content": favorable data to the patient or physician, expert report, type of surgery, and complaint prices of sentences of the three studied States. RESULTS: The total number of lawsuit was higher in São Paulo (n = 156), followed by Rio Grande do Sul (n = 110) and Rio de Janeiro (n = 58), however, it was observed higher condemnation incidence of physician in Rio de Janeiro, followed by São Paulo and Rio Grande do Sul. CONCLUSIONS: the incidence of demands was distinctive in the three States over time. Complaints concerning dissatisfaction, in the States had a rate of (more than 50%) of dismissing the action, and the judgment of the increased price in cases followed by death to patient event. The largest amounts paid to patients took place in São Paulo. Patients with complaints of asymmetry and scar have a greater share of gain incidence.